Estrategias de marketing digital para el fortalecimiento de la empresa “Parrilladas y Pizzería la Casa del Gaucho” en el cantón Ambato, provincia Tungurahua, año 2022 - Hachi Alarcón, Patricio Sebastian (2022)
The company "PARRILLADAS Y PIZZERIA LA CASA DEL GAUCHO" is the branch of a business that emerged in the city of Guaranda in 2010. The branch is located in the city of Ambato, where 5 people work, for its opening, a thorough market study and analysis of the different factors that may or may not affect the company was not carried out. Although the establishment operates in an area where there are several competitors and must face the harsh conditions of the current market, the strengths and opportunities have not been established which could be exploited in order to maintain a differentiation from its competition, these factors mentioned make the company require digital marketing strategies to stand out in the market. In order to find a solution to the problem, it is proposed as an objective to develop digital marketing strategies for the company "GRILLS AND PIZZERIA LA CASA DEL GAUCHO" IN AMBATO CANTON, TUNGURAHUA PROVINCE, YEAR 2022 ", starting with the external situational analysis where the factors and the positive or negative impact will be identified, after this analysis the strategic positioning matrix will be carried out where it will be determined if the company has competitive advantages, the SWOT matrix will be carried out in order to identify the different strengths, opportunities, weaknesses and threats in order to determine the shortcomings of the company. Within the study, the inductive and deductive methods will be carried out, which will help to collect relevant information for the investigation, considering a population of 313,018 inhabitants, which belong to the economically active population of the Ambato canton, the sample size formula will be applied. which will contribute with information for the current investigation.